Dual-parameter identification based on model reference adaptive system for five-phase induction motor - Xinguo HOU; Xiangyu LUO; Xuan TU (电力工程技术, 2025)
The five-phase induction motor, known for its simplicity among multiphase induction motors, offers benefits such as low noise, minimal torque ripple, and high load capacity, rendering it suitable for applications demanding high power and reliability. To counter the vulnerability of speed encoders to external disturbances, a model reference adaptive system (MRAS) without speed sensor vector control system is devised for five-phase induction motors to enable speed identification and achieve sensorless control. Subsequently, a dual-parameter identification system is developed based on MRAS to address the dependency of the traditional MRAS's magnetic flux reference model on stator resistance values, allowing for the simultaneous identification of speed and stator resistance with adaptive rate calculations for each parameter. The simulation of this dual-parameter identification system using Simulink demonstrates excellent speed identification performance across a range of speeds and load torques, with minimal overall identification errors and steady-state fluctuations of around 9.7 r/min. When encountering abrupt changes in stator resistance under transient load conditions, the identification error remains below 5%, showing errors of 8.7% at half-load and 13.7% at full-load.